SETTLEMENT OF DIVORCE FROM INTERRELIGIONS AND ITS LEGAL CONSEQUENCES ACCORDING TO NATIONAL CIVIL LAW - Ayu Herlin Norma Yunita (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
In marriage different religions the same goes for marriage normal in it contain problem social and juridical . Divorce as a incident although allowed but as a things that Allah does not like . This shows as close as possible existing marriage happen , don't let it break Because divorce. According to Article 38 of the Law Number 1 of 1974 concerning Marriage states that something marriage can separated Because death , divorce and above decision Court . Divorce is he decided something bond marriage between husband wife by the way through decision court and there is Enough reason that between husband and wife cannot life reconcile as husbands wife , who became complicated when divorce the from marriages of different religions. The problems that arise are not only about division treasure together will but also rights nurturing and nurturing child in divorce different religions.